THE FANTASTIC ELEMENTS OF HARRY POTTER: A MAGICAL JOURNEY - Bobonazarova Anora Kakhramonovna (Scholar Express Journal, 2023)
The article unravels the layers of the writer’s imagination. It examines how magical objects serve not only as plot devices but as conduits to a world where the extraordinary is an integral part of daily life. Through this exploration, readers are invited to believe in the magic that lies within the pages, transcending fiction into a realm where the fantastical becomes tangible. Those elements are investigated from an extensive point of view as well as necessary examples are also given in detail.
Keywords: Harry Potter series; J.K. Rowling’s wizarding world; mythical creatures in Harry Potter